ANALISIS KINERJA KOPERASI - Adhisyahfitri Evalina Ikhsan (PEKBIS, 2013)
The objective of this research is to analyze wheter internal and external factorsinfluence the cooperative performance in Banda Aceh and Aceh Besar. And wheterthere is increasing on cooperative performance which receives capital aid from BRR.Populations of this research were 36 cooperative in Banda Aceh and Aceh Besarwhich receive capital aid from BRR. The sources of data were taken fromcooperative financial statement. Data used in this research were cooperativeperformance, amount of numbers, human resources, rentability, profitability, likuidity,solvability and activity. Data were analyzed by using mean test. The result of thisresearch showed that there is decreasing on cooperative performances whichreceive capital aid from BRR. And then there is increasing on amount of members,cooperative likuidity and decreasing on amount of employee, rentability, profitability,solvability and activity.Keywords : Internal factor, external factor, cooperative performance